ISLAMIC DA‘WAH AND LOCAL WISDOM AS A STRATEGY FOR SOCIAL HARMONY IN MUSLIM COMMUNITIES: A QUALITATIVE PHENOMENOLOGICAL STUDY IN INDONESIA - Muhammad Ismail; Yusron Razak (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
This study investigates the strategic role of Islamic da‘wah integrated with local wisdom in fostering social harmony within Muslim communities across diverse regions of Indonesia. In an era marked by rising religious polarization, digital misinformation, and socio-cultural fragmentation, the integration of Islamic communicative traditions with indigenous values offers a sustainable and contextually grounded approach to communal peace-building. Employing a qualitative phenomenological design, data were gathered from 42 participants across five Indonesian provinces through in-depth interviews, participant observation, and documentary analysis over a 12-month period (January–December 2023). Thematic analysis guided by the framework of Moustakas (1994) was used to interpret participants’ lived experiences. The findings reveal four interconnected themes: (1) the organic embedding of local values such as gotong royong (collective cooperation), musyawarah (deliberative consensus), and tepo seliro (mutual empathy) into da‘wah discourses; (2) the pivotal role of ulama (religious scholars) and mosque institutions as socially trusted mediators; (3) culturally adaptive da‘wah as a preventive mechanism against religious extremism; and (4) significant intergenerational and digital challenges confronting contemporary practitioners. This study demonstrates that local wisdom-based da‘wah is not merely a rhetorical adaptation but a structural strategy for building inclusive, moderate, and harmonious Muslim communities. The findings carry theoretical implications for Islamic communication theory, sociology of religion, and multicultural education, while offering practical recommendations for religious institutions and policy makers.